Optimization on Epoxidation of Palm Olein by Using Performic Acid - Darfizzi Derawi; Jumat Salimon (E-Journal of Chemistry)
The epoxidation process of palm olein (POo) was carried out by using in situ generated performic acid (HCOOOH) to produce epoxidized palm olein (EPO). HCOOOH was produced by mixing of formic acid (HCOOH) as oxygen carrier and hydrogen peroxide (H2O2) as oxygen donor in various ratio of POo: HCOOH: H2O2. The effect of HCOOH and H2O2 concentration, temperature, stirring effect and reaction time were studied. The presence of oxirane ring of EPO was characterised by fourier transformation infra-red (FTIR), proton and carbon nuclear magnetic resonance (1H-NMR and (13C-NMR) spectra. The results showed that an optimum oxirane oxygen content (OOC) value was obtained by using mol ratio of 1: 5: 2 at 150 minutes.